Cotton certification in Ethiopia: Can an increasing demand for certified textiles create a 'fashion revolution'?. Issue 99 (February 2019) - Partzsch, Lena; Kemper, Laura
Highlights: Certification programs promise the sustainability of the cotton revival in Ethiopia. GOTS gives ethically conscious consumers the power to resist 'fast fashion' CmiA stands for power with conventional producers, retailers and consumers. GOTS is more radical, but the 'fashion revolution' is limited to niche markets. Both initiatives fail to turn over conventional cotton agriculture and trade. Abstract: Ethiopia is witnessing a cotton revival. Voluntary certification programs, such as the Global Organic Textile Standard (GOTS) and Cotton made in Africa (CmiA), promise to ensure the sustainability of this development. When advertising certification, companies call upon consumers to 'join the fashion revolution' and overcome grievances of 'dirty fashion'. We are interested in the types of relations through which certification initiatives can facilitate a transition to greater sustainability. So far, scholars have shown that sustainability certification emerges from a neoliberal agenda and therefore reproduces asymmetries. Complementing these studies, we make a strong claim for acknowledging the capacity of agency or agents in the debate about power in certification. For this purpose, we use concepts of power to (empowerment and resistance) and power with (cooperation and learning) to explore the two cases of GOTS and CmiA. Both concepts represent different forms of exercising power and bringing about change. We find that GOTS offers consumers the opportunity to alter their position. They have the power to establish an alternative (niche) system of ethical trade. By contrast, CmiA represents power with conventional producers, retailers and consumers. This certification initiative can be considered less radical, but it has a much better market outreach. While we argue that only certification that demands the creation of alternative market structures can be a starting point for a 'revolutionary' transition, we also see a need for the conventional industry to change in countries such as Ethiopia.